Wage Effects on Immigrants from an Increase in the Minimum Wage Rate : An Analysis by Immigrant Industry Concentration - Kalena E. Cortes (Institute for the Study of Labor (IZA), 2004)
Using the monthly samples of the Current Population Survey (CPS) outgoing rotation group files, this paper analyzes the most recent increase in the U.S. minimum wage rate. This study focuses on immigrant and native-born workers who are employed in industries with low and high immigrant concentrations, and investigates whether there is any relationship between industry non-compliance and the concentration of immigrant workers. This study finds that resultant wage increases were equal for both immigrants and natives. Also, the analysis shows no existing evidence of non-compliance towards immigrant workers; but rather that female immigrants in immigrant-intensive industries (the worst off in the sample) are the workers with the highest compliance towards them.
Keywords: J10; J83; J82; J00; 330; minimum wage; immigrant workers; immigrant-intensive industries; minimum wage compliance; Mindestlohn; Normbefolgung; Migranten; Internationale Arbeitsmobilität; Frauenarbeitslohn; Branche; Schätzung; Vereinigte Staaten